Inactivation of Tnf‐α/Tnfr signaling attenuates progression of intervertebral disc degeneration in mice - Chu Tao; Sixiong Lin; Yujia Shi; Weiyuan Gong; Mingjue Chen; Jianglong Li; Peijun Zhang; Qing Yao; Dongyang Qian; Zemin Ling; Guozhi Xiao (JOR Spine)
Abstract Background Intervertebral disc degeneration (IVDD) is a major cause of low back pain (LBP), worsened by chronic inflammatory processes associated with aging. Tumor necrosis factor alpha (Tnf‐α) and its receptors, Tnf receptor type 1 (Tnfr1) and Tnf receptor type 2 (Tnfr2), are upregulated in IVDD. However, its pathologic mechanisms remain poorly defined. Methods To investigate the role of Tnfr in IVDD, we generated global Tnfr1/2 double knockout (KO) mice and age‐matched control C57BL/6 male mice, and analyzed intervertebral disc (IVD)‐related phenotypes of both genotypes under physiological conditions, aging, and lumbar spine instability (LSI) model through histological and immunofluorescence analyses and μCT imaging. Expression levels of key extracellular matrix (ECM) proteins in aged and LSI mice, especially markers of cell proliferation and apoptosis, were evaluated in aged (21‐month‐old) mice. Results At 4 months, KO and control mice showed no marked differences of IVDD‐related parameters. However, at 21 months of age, the loss of Tnfr expression significantly alleviated IVDD‐like phenotypes, including a significant increase in height of the nucleus pulposus (NPs) and reductions of endplates (EPs) porosity and histopathological scores, when compared to controls. Tnfr deficiency promoted anabolic metabolism of the ECM proteins and suppressed ECM catabolism. Tnfr loss largely inhibited hypertrophic differentiation, and, in the meantime, suppressed cell apoptosis and cellular senescence in the annulus fibrosis, NP, and EP tissues without affecting cell proliferation. Similar results were observed in the LSI model, where Tnfr deficiency significantly alleviated IVDD and enhanced ECM anabolic metabolism while suppressing catabolism. Conclusion The deletion of Tnfr mitigates age‐related and LSI‐induced IVDD, as evidenced by preserved IVD structure, and improved ECM integrity. These findings suggest a crucial role of Tnf‐α/Tnfr signaling in IVDD pathogenesis in mice. Targeting this pathway may be a novel strategy for IVDD prevention and treatment.